F4/80+ Host Macrophages Are a Barrier to Murine Embryonic Stem Cell-Derived Hematopoietic Progenitor Engraftment In Vivo - Heather L. Thompson; Nico van Rooijen; Bryce T. McLelland; Jennifer O. Manilay (Journal of Immunology Research)
Understanding how embryonic stem cells and their derivatives interact with the adult host immune system is critical to developing their therapeutic potential. Murine embryonic stem cell-derived hematopoietic progenitors (ESHPs) were generated via coculture with the bone marrow stromal cell line, OP9, and then transplanted into NOD.SCID.Common Gamma Chain (NSG) knockout mice, which lack B, T, and natural killer cells. Compared to control mice transplanted with adult lineage-negative bone marrow (Lin− BM) progenitors, ESHP-transplanted mice attained a low but significant level of donor hematopoietic chimerism. Based on our previous studies, we hypothesized that macrophages might contribute to the low engraftment of ESHPs in vivo. Enlarged spleens were observed in ESHP-transplanted mice and found to contain higher numbers of host F4/80+ macrophages compared to BM-transplanted controls. In vivo depletion of host macrophages using clodronate-loaded liposomes improved the ESHP-derived hematopoietic chimerism in the spleen but not in the BM. F4/80+ macrophages demonstrated a striking propensity to phagocytose ESHP targets in vitro. Taken together, these results suggest that macrophages are a barrier to both syngeneic and allogeneic ESHP engraftment in vivo.